Performance of three-layer composites with densified surface layers of Nothofagus pumilio and N. antarctica from Southern Patagonian forests. Issue 5 (20th October 2018) - Schwarzkopf, Matthew; Burnard, Michael; Martínez Pastur, Guillermo; Monelos, Lucas; Kutnar, Andreja
ABSTRACT: Nothofagus pumilio and N. antarctica forests of Southern Patagonia, Argentina are currently being managed for production of saw logs with fast growing conditions. The result of these management strategies is faster growing forests, but also an increase in the percentage of low-density wood. The motivation for this study was to find a way to valorise this low-density wood. Surface and bulk densification treatments were applied these wood species and were then applied as face layers in three-layer composites. The mechanical properties of three-layer composites were studied. The modulus of elasticity, modulus of rupture, and modulus of hardness were improved compared to many types of structural composite lumber. This increase in mechanical properties of N. pumilio and N. antarctica wood opens the possibility for its use in structural composites and added value to these otherwise underutilised and undervalued species.